The Use Of Read, Cover, Remember and Retell Strategy On Students’ English Reading Comprehension - Wieke Wido Wati (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
This research was aimed to find out whether there was significant effect of using read, cover, remember and retell (RCRR) strategy on students’ English reading comprehension. The design was a quasi-experimental research. The sample consisted of 60 students; 30 students for experiment group and 30 students for control group. The instrument was reading test which comprised 30 multiple choice (4 options) question with r=0,86 .The research finding were as follows; 1). RCRR strategy affected students’ reading comprehension in whole reading comprehension RCRR strategy affected students’ reading comprehension in various aspect of reading comprehension, 2). RCRR strategy affected the students’ reading comprehension in the aspect of finding main idea, 3).RCRR strategy affected the students’ reading comprehension in the aspect of making inference, 4).RCRR strategy affected the students’ reading comprehension in the aspect of understanding vocabulary and determining reference. However, RCRR strategy did not affect the students’ reading comprehension in the aspect of identifying specific information. Further study is recommended for medical school.